2023
DOI: 10.1101/2023.01.20.524893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole transcriptome profiling of placental pathobiology in SARS-CoV-2 pregnancies identifies placental dysfunction signatures

Abstract: Pregnant people infected with the SARS-CoV-2 virus have shown a higher incidence of "preeclampsia-like syndrome". Preeclampsia is a systematic syndrome that affects 5% of people worldwide and is the leading cause of maternal mortality. It is characterised by placental dysfunction, leading to poor placental perfusion, maternal hypertension and neurological disturbances. Here, we used whole-transcriptome, spatial profiling of placental tissues to analyse the expression of genes between placentae from pregnant pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…96 Notably, this study also identified the upregulation of HSPA1A, an alarmin previously reported to be linked with preeclampsia, 97 in the placenta of SARS-CoV-2-positive women, supporting the mechanistical link between SARS-CoV-2 and preeclampsia. 96 Spatial transcriptomic analysis comparing SARS-CoV-2 infected and non-infected placentas identified the enrichment of signatures associated with hypoxia and placenta dysfunction in SARS-CoV-2 infected placentas, 98 showing the similarity of local changes occurring in preeclampsia and SARS-CoV-2 infection. Using an in vitro STB model induced from trophoblast stem cells, another study demonstrated that SARS-CoV-2 infects the STB via ACE-2, an entry receptor of this virus, 99 leading to cytotoxicity and impaired differentiation of the STB model evaluated by fusion index and human chorionic gonadotropin (hCG) production.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…96 Notably, this study also identified the upregulation of HSPA1A, an alarmin previously reported to be linked with preeclampsia, 97 in the placenta of SARS-CoV-2-positive women, supporting the mechanistical link between SARS-CoV-2 and preeclampsia. 96 Spatial transcriptomic analysis comparing SARS-CoV-2 infected and non-infected placentas identified the enrichment of signatures associated with hypoxia and placenta dysfunction in SARS-CoV-2 infected placentas, 98 showing the similarity of local changes occurring in preeclampsia and SARS-CoV-2 infection. Using an in vitro STB model induced from trophoblast stem cells, another study demonstrated that SARS-CoV-2 infects the STB via ACE-2, an entry receptor of this virus, 99 leading to cytotoxicity and impaired differentiation of the STB model evaluated by fusion index and human chorionic gonadotropin (hCG) production.…”
Section: Sars-cov-2mentioning
confidence: 99%